Effect Of Capital, Liquidity, Efficiency, Performance On Profitability In Sharia Commercial Banks in Indonesia - SM, R. Bambang; Razimi, Moh. Sharil Bin Ahmad (IKONOMIKA, 2018)
This research target aims to determine the effect of capital, liquidity, efficiency, banking performance on profitability in Islamic Commercial Banks in Indonesia in 2013-2015. This type of research is quantitative descriptive research. In this study using secondary data, and the period of time used 3 years, namely the period 2013-2015. The sampling technique was purposive sampling. The research variables consisted of 5 variables (4 independent variables and 1 dependent variable). The research data was taken from the 2013-2015 period Islamic financial bank 11 financial statements. Validation of this research data was verified by publishing on each Sharia Commercial Bank website , the website of Bank Indonesia and the website of the Indonesian Central Bureau of Statistics. Data analysis used is Regression analysis to analyze the factors that influence the profitability of Islamic Commercial Banks in Indonesia in 2013-2015. Data analysis method uses Multiple Regression. Hypothesis testing uses F-statistic test (F test), t-statistic test and determination of Ajusted R² coefficient with a significance level of 5%.The results of the study are simultaneous independent variables (F test) that affect the profitability with a significant level of 0,000. While partially (t test) shows that: (1) capital has a positive and significant effect on profitability, (2) liquidity has a positive and significant influence on profitability, (3) efficiency has a negative and significant effect on profitability, (4) performance has a negative and significant influence on the profitability of Islamic Commercial Banks ..Based on the adjusted R² obtained 0.563 this means that the ability of four independent variables can explain Profitability 56.30% while the remaining 43.70% is explained by other factors. Keywords: Capital, Liquidity, Efficiency, Performance and Profitability